Microbiota and volatilome profile of fresh and chill-stored deepwater rose shrimp (Parapenaeus longirostris). (June 2020) - Parlapani, Foteini F.; Ferrocino, Ilario; Michailidou, Sofia; Argiriou, Anagnostis; Haroutounian, Serkos A.; Kokokiris, Lambros; Rantsiou, Kalliopi; Boziaris, Ioannis S.
Graphical abstract: Highlights: 16S meta-barcoding determined the microbiota in deepwater rose shrimp. Taxa associated with spoilage phenomenon or hygiene practice were revealed. Shrimp stored at 0 or 4 °C was characterized by the presence of particular VOCs. Psychrobacter and Carnobacterium dominated the chill-stored shrimp. Abstract: Bacterial communities and Volatile Organic Compounds (VOCs) profile of deepwater rose shrimp ( Parapenaeus longirostris ) stored at 0 °C (ice) and 4 °C were investigated using 16S amplicon based sequencing and Solid phase micro-extraction (SPME) - Gas chromatography/mass spectrometry (GC/MS), respectively. The shelf-life of shrimps determined by sensory assessment was 5 and 2 days at 0 °C and 4 °C, respectively. Based on 16S analysis (culture-independed), the initial microbiota of shrimps mainly consists of Photobacterium, Candidatus Hepatoplasma, Psychrobacter, Acinetobacter and Delftia. Psychrobacter and Carnobacterium dominated during storage at both temperatures. Psychrobacter was the most dominant taxon at the end of shelf-life of chill-stored shrimps. A minor microbial population composed by Brevundimonas, Stenotrophomonas, Staphylococcus, Legionella, Acinetobacter, Bacillus, Escherichia-Shigella, Enterococcus, Enterobacter, Klebsiella was also detected. Those taxa may be originated from the environment due to an inadequate hygienic practice during fishing, handling and icing. VOCs such as ethanol, 3-methyl-1-butanol, 2-ethyl-1-hexanol, 3-hydroxy-2-butanone, indole etc., were found to be associated with shrimps at 4 °C, while acetone and dimethyl sulfide with shrimps in ice. Some VOCs, from microbial or chemical origin, increased in shrimps either at 0 °C (i.e. 1-octen-3-ol, trans-2-octenal) or at 4 °C (i.e. 3-methyl-1-butanol, indole), while 2-methylbutanal and 3-methylbutanal increased in both temperatures. A positive correlation between Psychrobacter with 2-ethyl-1-hexanol and Carnobacterium with 3-methyl-1-butanol was also observed. Concluding, we suggest the reinforcement of Good Hygiene Practices on fishing boats during fishing/handling, the rapid onboard icing and keeping shrimps iced avoiding even small increase of storage temperature that affects quality parameters (e.g. microbial population level, synthesis of microbiota, VOCs profile) in order to provide a product of the highest quality and safety in the market.